Urbanisation and Infrastructural Development in Nagaland: A Case Study of Kohima and Mokokchung District - Chubakumzuk Jamir (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
Urbanisation is now becoming a global phenomenon, high rate of population growth; declining opportunities in rural areas and shift from stagnant and low paying agriculture sector to more paying urban occupations, largely contribute to urbanization process. This paper studies the level of physical and social infrastructural progress in Kohima and Mokokchung districts using seven indicators such as education institution, health, banking, postal service, water supply, surface road cover and electricity. Research survey was conducted in Kohima and Mokokchung in 2017-18. The sample wards were selected using random sampling methods. The data’s collected were than analyzed using Principal Components Analysis Model. The findings shows that 50% of urban areas are in developed and 37.5% in moderately developed and 12% in less developed with regard to surface road, medical facilities, education, postal service, banking and water supply. The study highlights that urbanisation has positive impact on infrastructure development in sample districts. The study also found the urban areas of Kohima are in leading position than Mokokchung with regard to social and physical infrastructure. The paper concludes by suggesting suitable policies for developing and less developed areas. Keywords: Urbanisation, Social and Physical Infrastructure